Road as a desiring machine: The development of Lintas Bono Road and social transformation in Kampar Peninsula, Riau - Hidayat, Fahri (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
There is much research on the impact of infrastructure development, especially roads in Indonesia. This in general only focuses on the social transformation based on the economic changes of the community. These research show the social transformation as the impact of the road infrastructure development projects goes beyond economic changes. Using the perspective of a critical study of development anthropology, the author discusses the impact of Lintas Bono Road infrastructure development project in Pelalawan Regency, Riau Province to the social transformation of the surrounding communities. This study used an ethnographic method to conduct observations and interviews with the stakeholders and communities around the Lintas Bono Road infrastructure development project. This project, which develops by the Kampar River flow, has opened road access to many coastal villages of Kampar River. This condition has triggered changes in public transportation modes, trade patterns for agricultural products, ethnic composition, and the land tenurial system in affected villages. The fact that the construction of this road has not been completed after seventeen years does not make the community reject this development. The shortcomings and failures of these developments have actually made the development of this road as a